Moving Horizon Planning for Human-Robot Interaction - Renz, Heiko; Kramer, Maximilian; Bertram, Torsten (2024 19th ACM/IEEE International Conference on Human-Robot Interaction (HRI), 2024)
The collaboration and interaction between humans and robots intensify with ongoing research and industry needs. Robots require a motion planner that contributes to a safe environment for humans. This paper provides the online trajectory planner Moving Horizon Planning for Human-Robot Interaction (MHP4HRI), customizable for various robots, considering obstacles and humans in their environment. The planner generates motion commands in a moving horizon manner, similar to Model Predictive Control. This enables robots to react to dynamic changes in the environment in real-time. Descriptions of the planner and the underlying algorithms are given, as well as details about the provided framework regarding the benefits and usage for the community. Furthermore, we aim to provide a growing framework with new features in the future regarding the optimization and interaction with the environment, especially humans. The code, implemented mainly in C++ for the Robot Operating System (ROS), is available at GitHub: https://github.com/rst-tu-dortmund/mhp4hri.CCS CONCEPTS* Computer systems organization → Robotic control; External interfaces for robotics; * Human-centered computing → Collaborative interaction.